Neurocysticercosis. Case report. - Gilberto Serrano Ocaña; Luz Maria Serrano Ocaña; Leonardo Almaguer Arena (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
A female patient (15 years), from Eastern Cape, South Africa, was admitted in the hospital on July 13th, 2007 with general tonic-clonic convulsions. There was not history of epilepsy or fever convulsions and the patient denied alcohol, cigar or drugs consumption. The physical examination showed postictal confusion, without neurological deficit, neck rigidity or peripheral edema. Computer axial tomography was definitive for neurocysticercosis disgnosis. Since it is a serious health problem for the area the patient lives in, we decided to publish the case.